EFFECT OF HARDENING TO DROUGHT TOLERANCE ON THE MOISTURE CONTENT OF SUNFLOWER PLANT. I. MOISTURE PERCENTAGEIN ROOT AND STEM (Baghdad Science Journal, 2008)
Two field experiments were conducted during the spring seasons of 2000,2001.The aim was to study the effect of hardening to drought tolerance on moisture percentage in root and stem of sunflower plant during growth stages . Asplit-split plots design was used with three replications.The main plots included irrigation treatments:irrigation to100%(full irrigation),75and50%of available soil water.The sub plots were the cultivars Euroflor and Flame.The sub-sub plots represented four seed soaking treatments :Control(unsoaked),soaking in water ,Paclobutrazol solution(250ppm),and Pix solution(500ppm). The soaking continued for 24 hours then seeds were dried at room temperature until they regained their original weight. Amount of water for each irrigation were calculated to satisfy water depletion in soil using a neutron meter. . Results indicated that stress at 800 Kp reduced moisture percentage in the root by 15.96% compared with full irrigation after86 days from planting,and in the stem by 9.64 and 11.99%compared with full irrigation and stress 600 Kp, respectively after 72 days from planting in the season 2001.Also stress 600 Kp reduced moisture percentage in the root after 58 days from planting by 5.81 and 5.97% compared with full irrigation and stress 800 Kp as a mean of seasons. Euroflor was superior over Flame after30 days from planting in the moisture percentage of its roots by 6.78 in the season of 2000 and by 3.10% as a mean of seasons..While Flame was superior in the moisture percentage of its stems by 4.62 and 2.51% after 58 days from planting in the season of 2000 and as a mean of seasons, respectively.Unsoaked treatment gave highest moisture percentage in the root, the percentage of increase reached to 5.05 and 9.63% than soaking in water and paclobutrazol after 30 days from planting and by 11.43 and 10.65% than soaked in water and pix solution after 86 days from planting as a mean of seasons. soaking in paclobutrazol solution decreased moisture percentage in the stem after 30 days from planting by 4.43 and 8.31% in the season 2000 and by 2.82 and 3.23% as a mean of seasons compared with soaking in water and pix solution , respectively. On the other hand paclobutrazol increased the percentage of moisture in the stems during the next stages of growth. The study suggest that it could improve water relations specially during the stages which increased water requirement (flowering and seeds filling), and increased drought tolerance by soaking the seeds presowing in water or plant growth regulators